2015
DOI: 10.1208/s12249-015-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stable Dry Powder Oxytocin Formulations for Delivery by Oral Inhalation

Abstract: In this work, heat stable dry powders of oxytocin (OT) suitable for delivery by oral inhalation were prepared. The OT dry powders were prepared by spray drying using excipients chosen to promote OT stability including trehalose, isoleucine, polyvinylpyrrolidone, citrate (sodium citrate and citric acid), and zinc salts (zinc chloride and zinc citrate). Characterization by laser diffraction indicated that the OT dry powders had a median particle size of 2 μm, making them suitable for delivery by inhalation. Aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…1) and recent data support a minimum 30 month shelf-life at 25 °C (approved by the UK Medicines & Healthcare products Regulatory Agency for clinical supply). An in vitro preclinical study further demonstrated that dry powder formulations of oxytocin suitable for oral inhalation can be prepared and are stable after extended storage under tropical and subtropical conditions ( Fabio et al, 2015 ). The potential for an IH powder form of oxytocin was also demonstrated in an in vivo preclinical study, which showed that administration of an ultra-fine oxytocin powder to the airways of postpartum sheep led to rapid absorption and comparable uterine electromyographic activity to that observed with IM administration ( Prankerd et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…1) and recent data support a minimum 30 month shelf-life at 25 °C (approved by the UK Medicines & Healthcare products Regulatory Agency for clinical supply). An in vitro preclinical study further demonstrated that dry powder formulations of oxytocin suitable for oral inhalation can be prepared and are stable after extended storage under tropical and subtropical conditions ( Fabio et al, 2015 ). The potential for an IH powder form of oxytocin was also demonstrated in an in vivo preclinical study, which showed that administration of an ultra-fine oxytocin powder to the airways of postpartum sheep led to rapid absorption and comparable uterine electromyographic activity to that observed with IM administration ( Prankerd et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the spray drying method is superior to fluid energy mill aided micronization in generating larger population of inhalable particles. Mankind Corporation reported a spray dried oxytocin DPI formulation having 77% of FPF at 30 L/min flow rate [56].…”
Section: In Vitro Lung Deposition Efficiency Evaluationmentioning
confidence: 99%
“…These include divalent metal ions in citrate and aspartate buffer solutions, 22–24,28 and dextrose and sodium chloride injection solutions 26 . Dry powder formulations have also been tested with excipients including trehalose, isoleucine, and polyvinylpyrrolidone along with citrate and zinc salts in an effort to make the solid state oxytocin stable in extreme hot climates 29 . Although some of these excipients have resulted in the enhancement of oxytocin stability, there is still room for further improvement.…”
Section: Introductionmentioning
confidence: 99%